2023
DOI: 10.1021/acs.jproteome.2c00430
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Is Characterized by Decreased Medium-Chain Acylcarnitines and Elevated Purine Degradation Metabolites across Pregnancy: A Case–Control Time-Course Analysis

Abstract: Gestational Diabetes Mellitus (GDM) results in complications affecting both mothers and their offspring. Metabolomic analysis across pregnancy provides an opportunity to better understand GDM pathophysiology. The objective was to conduct a metabolomics analysis of first and third trimester plasma samples to identify metabolic differences associated with GDM development. Forty pregnant women with overweight/obesity from a multisite clinical trial of a lifestyle intervention were included. Participants who devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Excessive fatty acid oxidation, depleted TCA intermediates and insulin resistance may cause overload of maternal mitochondria. This leads to incomplete fatty acid oxidation and an increase in plasma acylcarnitines, though acylcarnitines are noted to decrease as pregnancy progresses, possibly due to dietary changes ( 57 ).…”
Section: Subsectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive fatty acid oxidation, depleted TCA intermediates and insulin resistance may cause overload of maternal mitochondria. This leads to incomplete fatty acid oxidation and an increase in plasma acylcarnitines, though acylcarnitines are noted to decrease as pregnancy progresses, possibly due to dietary changes ( 57 ).…”
Section: Subsectionsmentioning
confidence: 99%
“…The kynurenine pathway, which produces nicotinamine adenine dinucleotide (NAD+) from tryptophan, is thought to be activated in GDM before placental hormones can produce a physiological effect ( 56 ). Increased levels of purine degradation metabolites (inosine monophosphate and hypoxanthine) are also seen in GDM, T1D and T2D ( 57 ). Uric acid is a downstream product of hypoxanthine oxidation which is commonly seen in diabetes, attributed to be due to concurrent generation of superoxide anions associated with increased inflammation and impaired insulin secretion ( 57 ).…”
Section: Subsectionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 In some studies on plasma purine degradation metabolites, similar results have shown that xanthine, hypoxanthine, and inosine monophosphate (IMP) are elevated in GDM patients. 94 , 95 A meta-analysis including 11 observational studies found that the level of serum uric acid in GDM patients was higher and correlated positively with an increased risk of GDM, especially in the first trimester. 96 Therefore, a model to elucidate the role of tryptophan and purine metabolism in the pathogenesis and pathophysiology of GDM is hypothesized.…”
Section: Urine Metabolomicsmentioning
confidence: 99%